Cementitious matrix made with processed glass waste - Matias, Camila Emanuelly da Silva; Lopes, Giuliene Pereira; Alves Barros, Samea Valensca (Latin American Journal of Energy Research, 2025)
The investigation into the technical feasibility of transforming glass waste into raw material for the production of alternative mortars corroborates the practice of Sustainable Development Goal number 12 (SDG 12). Thus, this study aimed to evaluate the influence of the use of glass waste collected in the municipality of Mossoró/RN on the simple compression resistance of masonry mortars, as well as on their behavior in the water absorption test. The methodological procedures for processing the waste used consisted of the use of grinding and sieving techniques. The preparation of alternative mortars was carried out using cylindrical molds with dimensions (50 X 100) mm with partial replacement levels of Portland cement of 10% and 15%. The simple compressive strength was determined following the procedures prescribed in NBR 7215 (ABNT, 2019) and water absorption according to NBR 9778 (ABNT, 2005). The results obtained demonstrated the technical feasibility of the parameters determined in this research. And that the increase in the replacement content of Portland cement with processed glass waste resulted in lower water absorption, which corresponds to an important characteristic for the durability of the proposed mortars against environmental chemical attacks, although it did not result in a gain in simple compression resistance, the values ​​​​were within the values ​​​​permitted for use in masonry completion mortar according to NBR 13281-2 (ABNT, 2023).
Keywords: Alternative mortars; AEC industry sustainability; Sustainable production; SDGs; Technical performance